Analisis Finansial Usaha Budidaya Tambak Polikultur Udang Windu (Penaeus monodon) dan Ikan Bandeng (Chanos chanos) di Desa Simpang Tiga Abadi Kabupaten OKI, Sumatera Selatan - Isnaini .; Fitri Agustriani (UNIVERSITAS SRIWIJAYA, 2013)
Business Development of fisheries in Ogan Komering Ilir highly prospective in terms oftechnical, social, economic, and available resources. Ogan Komering Ilir district, especially Simpang Tigavillage, Tulung Selapan subdistrict have developed tiger shrimp and milkfish in polyculture. This studyaimed to determine the business analysis of tiger shrimp and milkfish cultivation pond polyculture anddetermine the appropriateness of the investment criteria of tiger shrimp and milkfish cultivation pondpolyculture in shrimp fishing in Simpang Tiga village, Tulung Selapan subdistrict, OKI South Sumatradistrict in November-December 2012. Questionnaire method used in this study with a sample of 32farmers and farm owners. The results of the business feasibility analysis show that the income of tigershrimp and milkfish cultivation pond polyculture in Simpang Tiga Abadi village, Ogan Komering Ilirdistrict is Rp 49,135,000 per year, while total expense amounting to Rp 27,671,320 and benefit value isRp 21,463,680 so that the tiger shrimp and milkfish cultivation pond polyculture got profit. NPV value isRp 62,263,009.28, Net B / C 2.19 and IRR value obtained 42%, then the NPV> 0, Net B / C â‰¥ 1, and theIRR> discount rate, so that the tiger shrimp and milkfish cultivation pond polyculture is feasible for theforeseeable future.Keywords: Financial Analysis, Simpang Tiga Abadi village, pond polyculture.